A Study to Identify the Potential Challenges in Entrepreneurial Endeavour by Marginalized Women of India - Mishra, Dr Mrigendra Nath (The journal of contemporary issues in business and government, 2023)
Marginalization is one of the forms of gender inequality under various economic conditions and under the influence of unique historical, cultural, legal, and religious elements. To put it another way, women may be excluded from some jobs and occupations, incorporated into others, and marginalized in yet others. In every place and society, they are always marginalized in comparison to men. The objective of this study was to address identified research questions arising out of issues of (marginalised)women entrepreneurship in the India. Although the issue is not new, but it has become more relevant for further research enquiry, as policymakers are embarking upon it with more rigor than ever before. The findings of the research have dual implications. One, from the perspective of contributions to the literature and the other from the perspective of policy.Keeping in mind the research objectives and research questions to be answered, exploratory cum descriptive research method was used. The target population and respondents for the study includes all the women from the marginalised section of the society in urban and rural area of India. The convenience sampling is employed to gather data for further analysis. In order to expand the sample size 188, were usable after data cleaning. Primary data was collected through 27 closed ended questions, non-disguised and self-designed structured questionnaires. The responses have been obtained on five-point Likert type scale. Secondary data is collected through the website, annual reports, journals, publications, theses & dissertations, and other projects newspapers and magazines etc. The data gathered with the help of questionnaire has been analyzed using statistical techniques such as exploratory factors analysis, confirmatory factor analysis, SEM and chi square etc. on AMOS and SPSS 23.